2016
DOI: 10.3389/fnhum.2016.00134
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Related Offline Improvements in Gross Motor Task Performance Occur Under Free Recall Requirements

Abstract: Nocturnal sleep effects on memory consolidation following gross motor sequence learning were examined using a complex arm movement task. This task required participants to produce non-regular spatial patterns in the horizontal plane by successively fitting a small peg into different target-holes on an electronic pegboard. The respective reaching movements typically differed in amplitude and direction. Targets were visualized prior to each transport movement on a computer screen. With this task we tested 18 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 23 publications
4
12
0
Order By: Relevance
“…In fact, these authors found that sleep was required for those motor tasks where the performance was guided by explicit external cues, while implicit procedural skills, relying on internal information, benefited from wakefulness intervals. Examples from gross motor skills studies confirm that when an explicit help is provided, the performance improves after a night of sleep but not following wakefulness intervals 23 , 31 , 33 , 40 . Conversely, an effect from time intervals during wakefulness appears when subjects perform complex motor tasks using implicit processes 32 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these authors found that sleep was required for those motor tasks where the performance was guided by explicit external cues, while implicit procedural skills, relying on internal information, benefited from wakefulness intervals. Examples from gross motor skills studies confirm that when an explicit help is provided, the performance improves after a night of sleep but not following wakefulness intervals 23 , 31 , 33 , 40 . Conversely, an effect from time intervals during wakefulness appears when subjects perform complex motor tasks using implicit processes 32 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The same sequence had been used in a previous study (Malangré and Blischke, 2016). In this study, sleep-related offline learning had been found when the participants were retested under free recall conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Performance gains after nocturnal sleep have also been demonstrated at unimanual tasks. Malangre and Blischke [ 73 ] and Malangre et al [ 74 ] employed a pegboard task on an electronic board where a sequence of gross reaching movements including the joints of the wrist, elbow, and shoulder were performed with the nondominant hand in the horizontal plane. One group practiced in the morning, the second in the evening.…”
Section: Effects Of Sleep On Gross Motor Learningmentioning
confidence: 99%
“…One group practiced in the morning, the second in the evening. Retests were carried out 15 min after acquisition in order to control the early retention as well as after 12 and 24 hours [ 73 ]. Mean execution time along all retests was reduced after nocturnal sleep but not after the wake periods.…”
Section: Effects Of Sleep On Gross Motor Learningmentioning
confidence: 99%
See 1 more Smart Citation